Serum ferritin as a crucial biomarker in the diagnosis and prognosis of intravenous immunoglobulin resistance and coronary artery lesions in Kawasaki disease: A systematic review and meta-analysis - Wen, Huai; Hun, Marady; Zhao, Mingyi; Han, Phanna; He, Qingnan (Frontiers in Medicine, 2022)
Early identification and treatment are paramount for IVIG resistance and CALs in patients with KD. Unfortunately, there is no single crucial biomarker to identify these patients in a timely manner, which makes KD the most common cause of acquired heart disease in children in developed countries. Recently, many studies have focused on the association between serum ferritin and IVIG resistance and CALs in KD. We thus performed a systematic review and meta-analysis to ascertain the diagnostic and prognostic value of SF in predicting IVIG resistance and CALs in KD in the acute phase. The pooled sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR), diagnostic odds ratio (DOR), and area under the receiver operating characteristic curve (AUC) were extracted from the data to evaluate the SF levels in KD. The hazard ratios (HRs) of related risk factors and their corresponding 95% confidence intervals (CIs) were applied to compute the pooled assessments of the outcomes. A total of 11 articles were included in this meta-analysis, including 20 studies for diagnosis and 5 studies for prognosis. In terms of diagnostic values, SF could identify KD patients in the overall studies with a relatively high pooled sensitivity, specificity, PLR, NLR, DOR, and AUC of 0.76 (95% CI: 0.69-0.82), 0.82 (95% CI: 0.76-0.88), 4.33 (95% CI: 3.07-6.11), 0.29 (95% CI: 0.22-0.38), 15.0 (95% CI: 9.00-25.00), and 0.86 (95% CI: 0.83–0.89), respectively. In studies comparing KD patients and controls, there was a relatively high pooled sensitivity, specificity, PLR, NLR, DOR, and AUC of 0.79 (95% CI: 0.72-0.84), 0.84 (95% CI: 0.79-0.91), 4.61 (95% CI: 3.27–6.51), 0.26 (95% CI: 0.20–0.34), 20.82 (95% CI: 11.83–36.64), and 0.89 (95% CI: 0.86–0.91), respectively. For the prognostic values, we found poor survival outcomes based on KD patients (HR = 1.31, 95% CI: 1.07-1.59, P = 0.008). Our meta-analysis suggests that SF may be used as a workable and critical biomarker for the diagnosis and prognosis of IVIG resistance and CALs in patients with KD. We also propose that maintaining the dynamic balance between iron, SF and ferroptosis will be an important therapeutic strategy to reduce the morbidity of CALs.